Existence of Solutions for a Class of Abstract Neutral Differential Equations - Henriquez-Miranda, H (American Institute of Mathematical Sciences, 2017)
This paper is devoted to studying the existence of solutions for a general class of abstract neutral functional differential equations of first order with finite delay. Specifically, we distinguish among mild, strong and classical solutions, and we characterize in terms of the forcing function of the equation the existence of solutions of each one of these types.